Influence of 2, 1‐erythro regiodefects on the crystallization behavior of isotactic polypropylene. Issue 3 (24th September 2018) - Tranchida, D.; Resconi, L.
Abstract: We produced isotactic polypropylene (iPP) samples with metallocene catalysts, containing 2, 1‐erythro regiodefects between ∼0% and 3.4% and only trace amounts of stereodefects, and studied their thermal properties in order to quantify the influence of regiodefects on the crystallization behavior of iPP. Isothermal and nonisothermal experiments performed on these samples show that increasing the regiodefects content proportionally slows down crystallization rate, apparently without phase transitions or additional phenomena. The analysis of the rigid amorphous fraction and the mobile amorphous fraction however reveals a different behavior of samples containing more than ∼1.5% regiodefects, related to the inclusion of these defects in the lamellae. Additionally, the wide range of regiodefects and a novel calculation approach allowed us to estimate the equilibrium melting temperature of a fully iPP free of defects to be 206°C . Abstract : The crystallization kinetics—both isothermal and nonisothermal—of a set of novel isotactic polypropylenes has been investigated. These samples are characterized by the absence of stereodefects, and either the absence or a very high content of 2, 1‐erythro regiodefects, that is, up to 3.4%. An attempt at investigating the amorphous phase and the possible location of 2, 1 regiodefects within is also provided.